2021
DOI: 10.1007/s41748-021-00250-5
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes in Climate Extremes Using CMIP6 Simulations Over SREX Regions

Abstract: This paper presents projected changes in extreme temperature and precipitation events by using Coupled Model Intercomparison Project phase 6 (CMIP6) data for mid-century (2036–2065) and end-century (2070–2099) periods with respect to the reference period (1985–2014). Four indices namely, Annual maximum of maximum temperature (TXx), Extreme heat wave days frequency (HWFI), Annual maximum consecutive 5-day precipitation (RX5day), and Consecutive Dry Days (CDD) were investigated under four socioeconomic scenarios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(57 citation statements)
references
References 62 publications
10
41
0
Order By: Relevance
“…Figure 2 Published in partnership with CECCR at King Abdulaziz University with relevant global (Sillmann et al 2013b) and regional (Lelieveld et al 2016) studies. These results are also in agreement with recent CMIP6 based studies (Vogel et al 2020;Almazroui et al 2021), in which similar patterns of warming have been reported. According to Almazroui et al (2021), the CMIP6 multimodel ensemble indicates a substantial increase in TXx over the Mediterranean region and adjacent parts of Europe, in contrast with areas near the tropics.…”
Section: Spatial Patternssupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 2 Published in partnership with CECCR at King Abdulaziz University with relevant global (Sillmann et al 2013b) and regional (Lelieveld et al 2016) studies. These results are also in agreement with recent CMIP6 based studies (Vogel et al 2020;Almazroui et al 2021), in which similar patterns of warming have been reported. According to Almazroui et al (2021), the CMIP6 multimodel ensemble indicates a substantial increase in TXx over the Mediterranean region and adjacent parts of Europe, in contrast with areas near the tropics.…”
Section: Spatial Patternssupporting
confidence: 93%
“…These results are also in agreement with recent CMIP6 based studies (Vogel et al 2020;Almazroui et al 2021), in which similar patterns of warming have been reported. According to Almazroui et al (2021), the CMIP6 multimodel ensemble indicates a substantial increase in TXx over the Mediterranean region and adjacent parts of Europe, in contrast with areas near the tropics. The stronger warming at the northern part of the MENA domain can be linked to soil moisture feedbacks (Russo et al 2019) and precipitation deficits (Mueller and Seneviratne 2012), which can amplify heat conditions.…”
Section: Spatial Patternssupporting
confidence: 93%
“…There are also high frequencies of extreme events such as droughts and floods [12][13][14][15][16][17]. Global projections show an increase in the frequency and intensity of precipitation and temperature extremes, with the increases related to an increase in greenhouse gas concentrations, according to a special report on managing the risk of extreme events and disasters to advance CC adaptation (SREX) [18]. The national oceanic and atmospheric administration (NOAA) of the United States of America declared that July 2021 was the hottest month in recorded history [19].…”
Section: Introductionmentioning
confidence: 99%
“…We also recognize that our results are based on the very high emissions scenario, SSP5‐8.5, which represents the worst‐case outcome. However, similar spatial patterns with smaller magnitude in the future changes are expected for lower emissions scenarios such as SSP2‐4.5 (Almazroui et al., 2021; Carvalho et al., 2021; IPCC, 2021). The issues discussed above should be taken into consideration when interpreting the CMIP6 simulations for regional long‐term planning.…”
Section: Discussionmentioning
confidence: 56%